Comparison of Minimally Invasive and Open Management of Cesarean Wound Complications: A Retrospective Chart Review [08N]. (May 2020) - Qadri, Farnoosh; Khan, Ayesha; Al-azawi, Hind; Sengstock, David; Chehab, Monzer
Abstract : INTRODUCTION: Superficial abscesses are common surgical site infections (SSI) following cesarean sections. Standard of care is open drainage but optimal management is not known. We compared superficial abscess (SA) management by image guided (IG) percutaneous drainage to open surgical (OS) drainage. METHODS: We performed a retrospective chart review between 1/1/2010 and 12/31/2018 of SSI following cesarean section. IRB waiver was obtained. All patients with SA measuring >3 cm by CT or ultrasound were included. Endpoints included: length of stay (LOS), opioids on discharge, and need for home health care or readmission (combined outcome). RESULTS: Of 2, 000 charts, n=8 IG (32%) and n=17 OS (68%) met inclusion criteria. Compared to IG patients, OS were significantly older (27.6±4.2 vs 33±6.0 years, P <.05), but had similar BMI (35.2±10.8 vs 39.8±10.2 kg/m 2, P >.1), smoking (25% vs 24%, P >.1), hypertension (38% vs 29%, P >.1), diabetes (13% vs 47%, P >.1), parity (2.8±2.5 vs 1.8±1 births, P >.1). Although antibiotic use was lower in OS group (3±1.9 vs 3.7±1.0, P >.1) and a suggestion of lower LOS (6.0±4.0 vs 5.0±2.3, P >.1), IG patients showed a trend of less home-care or readmissions (38% vs 65%, P >.1). Significantly, IG patients were discharged less frequently on opiates (40% vs 88%, P <.01). CONCLUSION: This study suggests that minimally invasive drainage of SA following cesarean section is a viable option and may be preferable in certain situations. Although, limited by small sample size, IG appears less painful than OS drainage. The difference in the outcome of home-care or readmissions was lower, though not statistically significant and deserves further study.